PELATIHAN PENGOLAHAN LIMBAH PERTANIAN-PETERNAKAN MELALUI PEMBUATAN PUPUK ORGANIK DI DESA PARIGI KABUPATEN WAJO - sema sema (MALLOMO: Journal of Community Service, 2025)
Agricultural and livestock waste can serve as a source of raw materials for organic fertilizer. This waste is highly potential due to its abundant availability, yet its utilization has not been optimized to support community needs. Therefore, a community empowerment program was implemented through the production of organic fertilizer from agricultural and livestock waste. The objective of this program is to process waste into organic fertilizer to improve community welfare in Parigi Village, Takalalla Sub-district, Wajo Regency. The approach used included program socialization, counseling, theoretical and practical training, as well as assistance in the production of organic fertilizer from waste. The results of the program showed that participants demonstrated good social skills and cooperation in completing tasks. Even outside of the training sessions, their social skills were evident. The organic fertilizer produced through waste fermentation proved useful in addressing fertilizer shortages and in restoring soil fertility and environmental health. Furthermore, the counseling and training activities ran smoothly and were beneficial in fostering independence in organic fertilizer production based on agricultural and livestock waste, while also significantly increasing participants’ knowledge. Before the training, the average knowledge score was 28.75% (pre-test), and after the training it increased to 87.75% (post-test). Ongoing assistance is still needed to ensure the sustainability of the program in the future.